Factors affecting the purchase of local beverage product - Mohammad, Noorita; Setapa, Mariam; Rahman, Khairunnisa (Institut Pengurusan Penyelidikan, 2012)
This study was carried out to measure the extent to which product promotion through advertising by Small and Medium Industries (SMIs) influences consumer purchasing decisions. The study focuses specifically on promotion through advertising for SMI products. The outcomes of this research are essential for readers to understand the factors that influence consumers to purchase products. Furthermore, while the research acknowledges the relationship of the marketing mix—consisting of Product, Price, Promotion, and Place—towards consumer satisfaction, this specific study focuses on promotion via advertising. A quantitative method was employed in this study. The respondents consisted of 300 students from Universiti Teknologi MARA (UiTM) Johor and residents from the Segamat area. The results show that there is a significant relationship between promotion via advertising and consumer purchase intention regarding SMI beverage products.